USA and France: dynamics of cooperation and presidencies of D. Trump and E. Macron - Oksana Mitrofanova (Американська історія і політика, 2018)
The article is devoted to investigation of cooperation between presidents Donald Trump and Emmanuel Macron. The views of two presidents on global issues are studied; convergent and divergent elements of their positions regarding international questions have been highlighted. A certain discrepancy between the approaches of Trump and Macron in assessing the contemporary role of international organizations has been defined. The opposite stands of the two presidents have been revealed as follows: the policy of realism, protection of national interests and certain isolationism of D. Trump and the policy of idealism, interdependence and common resolving of the contemporary global issues of E. Macron. The approaches of Trump and Macron concerning the USA-France relations significance have been analyzed. The opposed positions of the two presidents towards the Paris agreement on climate change, which was signed by almost all countries of the world, have been highlighted.